Synthetic and anti-cancer activity aspects of 1, 3, 4-thiadiazole containing bioactive molecules: A concise review - Obakachi, Vincent A.; Kushwaha, Babita; Kushwaha, Narva Deshwar; Mokoena, Sithabile; Ganai, Ab Majeed; Pathan, Tabasum Khan; van Zyl, Werner E.; Karpoormath, Rajshekhar (Journal of sulfur chemistry, 2021)
Despite significant advances in understanding cancer pathogenesis, it continues to be one of the leading causes of death. Thus, there is an urgent need for the development of novel, more effective anticancer therapeutics. In recent years, small molecules containing five-member heterocyclic moieties have become the subject of considerable growing interest for designing new anticancer agents. An example is the 1,3,4-thiadiazole, a versatile scaffold widely studied in medicinal chemistry. The mesoionic character of the ring allows 1,3,4-thiadiazole-containing derivatives to cross the cellular membrane and interact strongly with biological targets leading to the possibility of low toxicity and high selectivity. This review attempts to collect the recent updates of synthetic methodology, structural activity relationship (SAR), and anticancer properties of 1,3,4-thiadiazole embedded derivatives, which can be considered potential anticancer agents.